2020
DOI: 10.1371/journal.pntd.0008469
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya virus requires an intact microtubule network for efficient viral genome delivery

Abstract: Chikungunya virus (CHIKV) is a re-emerging mosquito-borne alphavirus, which has rapidly spread around the globe thereby causing millions of infections. CHIKV is an enveloped virus belonging to the Togaviridae family and enters its host cell primarily via clathrin-mediated endocytosis. Upon internalization, the endocytic vesicle containing the virus particle moves through the cell and delivers the virus to early endosomes where membrane fusion is observed. Thereafter, the nucleocapsid dissociates and the viral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Early studies have shown that microtubules regulate virus infection (64). As pathogenic cargos, viruses require microtubules for transport to and from their intracellular sites of replication (65). Nocodazole disrupts microtubules and inhibits vesicular trafficking, including transport between early and late endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have shown that microtubules regulate virus infection (64). As pathogenic cargos, viruses require microtubules for transport to and from their intracellular sites of replication (65). Nocodazole disrupts microtubules and inhibits vesicular trafficking, including transport between early and late endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage of many cytoskeletal proteins likely contributes to altered virus and host component trafficking, yet cytoskeletal drugs have remained mostly ineffective against alphaviruses. These drugs may help prevent initial endocytosis, [56,57] internalization of replication complexes in spherules into cytopathic vacuoles, [58] and virion release, yet alphaviruses are known to still replicate in their presence. [59,60] In the extracellular matrix, the most obviously affected region in arthritis, nsP2pro likely cleaves many structural proteins.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti also suggests that tubulin is highly associated with DENV infection in the mosquito host with roles in transport and assembly ( Guo et al., 2010 ). In CHIKV infection, impaired viral delivery from the cell surface to the cytoplasm occurred when microtubule network is disrupted ( Hoornweg et al., 2020 ). While ZIKV’s effect on Ae.…”
Section: Molecular Interactions Between Arboviruses and Ae Aegyptimentioning
confidence: 99%
“…This is the first demonstration to confirm the direct involvement of Wolbachia in arbovirus binding and entry by taking advantage of the same host cytoskeletal proteins DENV and ZIKV utilize. Although there is a lack of data that demonstrates the same mechanism in CHIKV, this arbovirus necessitates an intact microtubule network consisting of alpha-tubulin (same family as beta-tubulin) for efficient viral entry and genome delivery to replication sites ( Hoornweg et al., 2020 ).…”
Section: Wolbachia As An Arboviral Inhibitormentioning
confidence: 99%